3-D coupled peridynamics and discrete element method for fracture and post-fracture behavior of soil-like materials. (June 2023) - Fukumoto, Yutaka; Shimbo, Taiki
Abstract: The present paper investigates a 3-D numerical analysis method, combining peridynamics (PD) and the discrete element method (DEM), which can simultaneously handle both the fracture and post-fracture behavior of materials assumed to be soils. With geomaterials, it is very important to treat the process from fracture to post-fracture in a continuous manner. The bond-based PD model is employed to reproduce the behavior from the initiation of cracks to fracturing. At the same time, the DEM model is also introduced so that the contact forces among the fragmented pieces can be calculated after the fracturing. The computational process of the physical contact between the wall element and the computational nodes of the PD is also solved based on the DEM so that plane geometry boundaries can be used. For the failure criteria of the connection between the computational nodes of the PD, a bilinear type of bond model is introduced to obtain a nonlinear stress–strain relationship and numerical stability when the calculation process switches from PD to the DEM. To verify the proposed approach, numerical simulations of the diametral compression test are performed on flawless cylindrical specimens, and the results are compared with theoretical solutions for the stress distribution inside the specimens. Based on the results, a simulation of the compressive failure of multiple soil-like crushable objects is performed as an example of the application of the coupled PD-DEM. The obtained results show that the proposed method will serve as a computational framework that can treat the continuous fracture behavior of soil-like materials in three dimensions.